If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -1c = 15 Solving 26 + -1c = 15 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + -1c = 15 + -26 Combine like terms: 26 + -26 = 0 0 + -1c = 15 + -26 -1c = 15 + -26 Combine like terms: 15 + -26 = -11 -1c = -11 Divide each side by '-1'. c = 11 Simplifying c = 11
| 2.4=3/5(b-5) | | 7/10x10-10=2/5 | | 8u+48= | | 12+x-(-5)=18 | | M/ | | 75=b/15 | | 85.5=9(m+3.3) | | 88+x+74-8x=180 | | X-3x+5(x+1)=38 | | -11=1+3r+r | | f(x)=3x^2+12x-4 | | (f)X=1-2x^3 | | X/2-4=15 | | 5x+20+3x+8=180 | | 5=b+5-6b | | 3(4x+1)=8x+4x | | -2n-8=4(-3n+2) | | -21+m=33 | | 1+3n=-6+5n-3n | | 3k+1-5=9k+12-8k | | 8y=16/3 | | X^2+3sinx=1.5 | | -4y+12=-48 | | -4y=12+x | | 6k^2+19k+11=-3 | | -17/42-1/6 | | 3(y-3)/3=2y | | 3=n+2+1 | | 3x=81/4 | | X+63=16 | | 1/4ln(1) | | 3/4x-36/4=3 |